Exploring the Impact of Effective Communication Strategies between Nursing and Medical Secretarial Teams on Patient Outcomes - Ahmed Mohammed Hussain Alzahrani(7)Yasir Abdulrazaq Abdullah Albuhayri(8)Mohammad Dakhel Hafez Alalyani(9)Shaher Saad Shaher Alqarni(10)Ghazi Maysha Majyul Alotaibi(11)Saad Obaid Saeed Al Elyani(12), Abdulrahman Hamed Saad Alqarni(1)Turki Hassan Ahmed Alomari(2)Humod Mohammed Ghaleb Almotairi(3)Salman Sulaman Safar Almotairi(4)Muhannad Mustafa Abed Alsayed(5)Ali Mohammed Awad Alghamdi(6) (Journal of Population Therapeutics and Clinical Pharmacology, 2022)
This research paper investigates the influence of efficient communication strategies between nursing and medical secretarial teams on patient outcomes. Effective communication between these two crucial healthcare units is vital for ensuring coordinated care delivery, optimizing patient safety, and improving overall healthcare quality. The paper examines various communication methods, barriers, and facilitators, along with their impact on patient satisfaction, clinical outcomes, and organizational performance. By exploring these factors, healthcare institutions can implement evidence-based strategies to enhance communication between nursing and medical secretarial teams, ultimately leading to improved patient outcomes.